Phosphatidylinositol 4-kinase β mutations cause nonsyndromic sensorineural deafness and inner ear malformation. (20th October 2020) - Su, Xiulan; Feng, Yufei; Rahman, Sofia A.; Wu, Shuilong; Li, Guoan; Rüschendorf, Franz; Zhao, Lei; Cui, Hongwei; Liang, Junqing; Fang, Liang; Hu, Hao; Froehler, Sebastian; et al.
Abstract: Congenital hearing loss is a common disorder worldwide. Heterogeneous gene variation accounts for approximately 20–25% of such patients. We investigated a five-generation Chinese family with autosomal-dominant nonsyndromic sensorineural hearing loss (SNHL). No wave was detected in the pure-tone audiometry, and the auditory brainstem response was absent in all patients. Computed tomography of the patients, as well as of two sporadic SNHL cases, showed bilateral inner ear anomaly, cochlear maldevelopment, absence of the osseous spiral lamina, and an enlarged vestibular aqueduct. Such findings were absent in nonaffected persons. We used linkage analysis and exome sequencing and uncovered a heterozygous missense mutation in the PI4KB gene (p.Gln121Arg) encoding phosphatidylinositol 4-kinase β (PI4KB) from the patients in this family. In addition, 3 missense PI4KB (p.Val434Gly, p.Glu667Lys, and p.Met739Arg) mutations were identified in five patients with nonsyndromic SNHL from 57 sporadic cases. No such mutations were present within 600 Chinese controls, the 1000 genome project, gnomAD, or similar databases. Depleting pi4kb mRNA expression in zebrafish caused inner ear abnormalities and audiosensory impairment, mimicking the patient phenotypes. Moreover, overexpression of 4 human missense PI4KB mutant mRNAs in zebrafish embryos resulted in impaired hearing function, suggesting dominant-negative effects. Taken together, our results reveal that PI4KB mutations can cause SNHL and inner ear malformation. PI4KB should be included in neonatal deafness screening.